If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -4(x + 2) = -8 + 5x + -33 Reorder the terms: 2x + -4(2 + x) = -8 + 5x + -33 2x + (2 * -4 + x * -4) = -8 + 5x + -33 2x + (-8 + -4x) = -8 + 5x + -33 Reorder the terms: -8 + 2x + -4x = -8 + 5x + -33 Combine like terms: 2x + -4x = -2x -8 + -2x = -8 + 5x + -33 Reorder the terms: -8 + -2x = -8 + -33 + 5x Combine like terms: -8 + -33 = -41 -8 + -2x = -41 + 5x Solving -8 + -2x = -41 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -8 + -2x + -5x = -41 + 5x + -5x Combine like terms: -2x + -5x = -7x -8 + -7x = -41 + 5x + -5x Combine like terms: 5x + -5x = 0 -8 + -7x = -41 + 0 -8 + -7x = -41 Add '8' to each side of the equation. -8 + 8 + -7x = -41 + 8 Combine like terms: -8 + 8 = 0 0 + -7x = -41 + 8 -7x = -41 + 8 Combine like terms: -41 + 8 = -33 -7x = -33 Divide each side by '-7'. x = 4.714285714 Simplifying x = 4.714285714
| 5+6*8+h=7*3+h | | 23-3m=5m+7 | | (2y^2+x)(y^2-7x)= | | (-1+6i)(3-5i)= | | 8[d+5]=12d-8 | | 3x-9=3(5-3x) | | 70-40+10x=12x+40-40 | | 3(x-3)-2(x+1)= | | 96t-16t^2-80=0 | | 5x+5=-115 | | 4+5x+9=7x-1 | | 4x^2-7x+11=9x+4 | | 0.75m+3=9 | | 2x-4(3-x)=7x+5 | | 5a-(2-a)=2a-14 | | 32t+-12=3t+42 | | 4[a+3]=2a+62 | | 24513465134+134613461= | | 19+t=-133 | | -14=w+3 | | 7z+14=5z+29 | | 18n=13 | | H=90-5t^2 | | 12=-4t | | 4+5x+9=7x+1 | | 8x+2=-6+3x+23 | | x^4+2x^2-36=0 | | (4x+5y)+(x+7y)= | | 1.5-0.04x=1.5 | | (x^2)-(2x)+(2)=0 | | 8+2=-6+3x+23 | | 5x+11y=-13 |